Feeding practices among children 6-23 months attending in an outpatient department of a tertiary level hospital in Dhaka - Rahman, Farhana; Rahman, Tasnova (International Journal of Research in Medical Sciences, 2025)
Background: As malnutrition is not considered a disease, it remains a hidden health problem and quietly steals energy, retards growth and development, and lowers body resistance to infection. This study aimed to assess the feeding practices among children aged 6-23 months attending the outpatient department (OPD). Methods: This cross-sectional study was conducted among 125 purposively selected mothers having children of 6 months to 2 years of age who attended the outpatient department of Holy Family Red Crescent Hospital. Face-to-face interview was done through questionnaires. Analysis of data was done with SPSS version 21. Results: Among 125 respondent’s majority (66.4%) had their first child at the age of between 18-22 years. Only some of them (35.2%) had antenatal check-ups during pregnancy and most (88.8%) of the mothers did not have postnatal care after the delivery of the last child. Regarding the reason for not taking PNC nearly all (91.0%) did not know PNC. Maximum (56.8%) knew about feeding colostrum after childbirth and most (88.8%) feed colostrum to their child and almost all (95.2%) of them were only breastfeeding their child for six months. Conclusions: The study highlighted a gap in maternal knowledge regarding antenatal and postnatal checkups, underscoring the need to raise awareness in these areas. However, most mothers demonstrated adequate awareness of proper breastfeeding practices, including colostrum feeding and complementary feeding.